Plan de negocio para la comercialización de chocolates artesanales en los establecimientos de Educación Básica, sector urbano en la ciudad de Latacunga - Mullo Mayo, Mary Yolanda (2015)
The general objective of the thesis project was to develop a business plan for the artisanal chocolates commercialization in basic education establishments, at urban sector in Latacunga city. The lack of knowledge and entrepreneurial support activities those have been the causes to that Latacunga doesn’t count with people are dedicated at handmade chocolates production and necessarily the product is purchased from big companies.